Mechanical and Shape Memory Properties of Additively Manufactured Polyurethane (PU)/Halloysite Nanotube (HNT) Nanocomposites - Nugroho, Wendy Triadji; Dong, Yu; Pramanik, Alokesh (MDPI AG, 2024)
This paper investigates the impact of halloysite nanotube (HNT) content on mechanical and shape memory properties of additively manufactured polyurethane (PU)/HNT nanocomposites. The inclusion of 8 wt% HNTs increases their tensile strength by 30.4% when compared with that of virgin PU at 44.75 MPa. Furthermore, consistently significant increases in tensile modulus, compressive strength and modulus, as well as specific energy absorption are also manifested by 47.2%, 34.0%, 125% and 72.7% relative to neat PU at 2.29 GPa, 3.88 MPa, 0.28 GPa and 0.44 kJ/kg respectively. However, increasing HNT content reduces lateral strain due to the restricted mobility of polymeric chains, leading to a decrease in negative Poisson’s ratio (NPR). As such, shape recovery ratio and time of PU/HNT nanocomposites are reduced by 9 and 45% with the inclusion of 10 wt% HNTs despite an increasing shape fixity ratio up to 12% relative to those of neat PU.